The Future of Work Requires More, Not Less Technology in Developing Countries - Raja, Siddhartha (World Bank, Washington, DC, 2017)
Digital technology is transforming the organization and location of production, and thus the futureof work. It risks widening the gap between richer and developing countries, and between the better skilled and connected and the poorer population groups within countries, who stand to bear the brunt of the adjustment. But technology also creates opportunities (leapfrogging), to generate jobs, increase earnings and be more inclusive. To take maximum advantage and counter the threat of rising global inequality, developing countries need to: (1) address bottlenecks in technology access; (2) invest in skills and (3) create an enabling environment.